Anti-adipogenic effect of oat hull extract containing tricin on 3T3-L1 adipocytes. Issue 12 (December 2015) - Lee, Dabeen; Park, Hyeong Yeol; Kim, Sohyun; Park, Yooheon; Bang, Myun-Ho; Imm, Jee-Young
Graphical abstract: Highlights: Oat hull extract showed significant anti-adipogenic activity in 3T3-L1 cells. Tricin was identified as a major active compound in the extract. Expression of adipocyte specific transcription factor genes was analyzed. Abstract: Oat hull ethyl acetate extract (50 μg/μL) significantly inhibited triglyceride accumulation in 3T3-L1 adipocytes without causing cytotoxicity. The major active compound in the extract was isolated and identified as 5, 7, 4′-trihydroxy-3′, 5′-dimethoxyflavone, tricin by mass spectrometry and 1H and 13 C NMR analyses. The tricin content in oat hull was approximately 18 mg/kg dry weight, and tricin constituted 9.6% of the total phenolic compounds in oat hull extract. The treatment of 3T3-L1 cells either with extract or purified tricin resulted in decreased lipid accumulation. The extract significantly decreased the activity of glycerol-3-phosphate dyhydrogenase, a marker of adipocyte differentiation in a dose dependent manner. The expression of major transcription factors, such as peroxisome proliferator-activated receptor (PPAR)-γ, CCATT/enhancer binding protein-α (CEBP/α), sterol regulatory binding protein 1 (SREBP1) and fatty acid synthase (FAS) was also significantly suppressed by the extract. When commercial purified tricin was added to 3T3-L1 cells the expression of all transcription factors were significantly decreased as low as 1.5 μg/μL treatment. These results suggest that oat hull extract containing tricin possesses anti-adipogeneic effect.